Outsourced attribute-based encryption with policy update - Su-qing LIN (网络与信息安全学报)
In order to achieve the efficient and flexible access control for the encrypted data stored in the cloud,an outsourced attribute-based encryption scheme with policy update was proposed.Based on the standard attribute-based encryption scheme,the functionality of policy update from delegation for a ciphertext without revealing any confidential information of the plaintext and private keys by utilizing the techniques of key blinding and outsourcing decryption was accomplished.Simultaneously,the decryption overhead for a user to recover the plaintext was effectively reduced.The scheme supports non-monotonic access structure and can be proved to have selective IND-CPA security and private key security under standard assumptions,respectively,in the standard model.Compared with similar schemes from literatures,the scheme provides better security and efficiency.